EVALUASI IMPLEMENTASI BIMBINGAN KONSELING KRISTEN DALAM MENDUKUNG PERKEMBANGAN PSIKOLOGIS PESERTA DIDIK - Milka Benyamin; Mirna Kanna'; Silva Ruben; Irmayanti Mangi'; Abigael Tangibali (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to evaluate the implementation of Christian counseling in supporting the psychological development of students in educational settings. The approach used was qualitative with descriptive evaluative methods through interviews, observation, and documentation. The results indicate that Christian counseling has a positive contribution in helping students manage emotions, build a healthy self-concept, and strengthen spiritual values. However, its implementation still faces various obstacles, such as limited counselor competence, lack of institutional support, and low student participation. The evaluation also showed that the integration of Christian values ​​into the counseling process is not yet fully optimal and still requires further development. Therefore, efforts are needed to improve the quality of the program through counselor training, strengthening school policies, and innovative service approaches. Thus, Christian counseling is expected to function more effectively in supporting the overall psychological development of students..